Multidisciplinary Approaches to Diabetes Mellitus Management: The Roles of Pharmacy, Nursing, Dentistry, Radiology, and Health Informatics-An Updated Review - Sumaili, Jameel Mohammed; Ali Hamad Mohamad Sumaili,; Badr Mohammed Kulaibi,; Afnan Nasser Alhadili,; Feras Saleh Dhaifallah Alsahli,; Khalid Abdulsamad Hafiz,; Mohammed Ahmed Ageeli,; Areej Ibrahim Hassan Faqiri,; Ahmed Nuwaifea Q. Aljohani,; Yahya Qasem Essa Mangari, (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Calibri, sans-serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Calibri, sans-serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Diabetes mellitus remains a global health crisis with rising prevalence and substantial morbidity, mortality, and healthcare costs. The complexity of diabetes care, particularly in patients with comorbidities, necessitates integrated, team-based approaches that extend beyond traditional physician-centered models. <span style="font-size: 12pt; font-family: Calibri, sans-serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Calibri, sans-serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to synthesize current evidence on multidisciplinary team (MDT) approaches in diabetes management, with specific focus on the evolving roles of pharmacy, nursing, dentistry, radiology, and health informatics professionals. <span style="font-size: 12pt; font-family: Calibri, sans-serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Calibri, sans-serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature search was conducted across PubMed, EMBASE, CINAHL, and Google Scholar for peer-reviewed studies published between 2020 and 2026. Studies evaluating MDT interventions in diabetes care, including the roles of pharmacists, nurses, dentists, radiologists, and health informatics specialists, were included. Data extraction and synthesis followed established review methodologies. <span style="font-size: 12pt; font-family: Calibri, sans-serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Calibri, sans-serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Evidence demonstrates that MDT approaches are associated with significant improvements in glycemic control, reduced complication rates, enhanced patient engagement, and cost-effectiveness. Pharmacists contribute through medication management and education, achieving HbA1c reductions of 0.05–2.1%. Nurses play central roles in patient education, remote monitoring, and care coordination. Dentists address the bidirectional relationship between periodontal disease and diabetes, though integration remains limited. Radiology professionals contribute through AI-enhanced imaging for complication detection. Health informatics enables data integration, clinical decision support, and coordinated care delivery. <span style="font-size: 12pt; font-family: Calibri, sans-serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Calibri, sans-serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Multidisciplinary team approaches are effective and cost-effective in diabetes management. Successful implementation requires professional training, digital infrastructure investment, and integrated care models. Future research should address cross-sectorial collaboration and scalable implementation strategies.